A Proposed Strategy for the Sports Activity in Some Iraqi Universities - Hameed Abd, Zeyad (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify the obstacles to the development of sports activity in some Iraqi universities through studying and knowing the objectives of the sports activity and sports program used, as well as the material and human resources available in some Iraqi universities. The two researchers used the descriptive methodology through the survey method as it suits the nature of the study. The sample, reaching 300 students, was selected randomly from among the students of some Iraqi universities. The two researchers used the questionnaire as a tool for data collection; it contained three axes under which (48) phrases were listed, with the most important results being the lack of clarity regarding the objectives of the sports activity, the weak program used by some universities, and the scarcity of material and human resources. The two researchers proposed a three-year strategy to promote the sports activity in some Iraqi universities along three stages from 2020 to 2023.